Anti-inflammatory and anti-nociceptive activities of the ethanolic extract of Annona muricata leaf - Abd Hamid @ Abdul Razak, Roslida; Tay, C. E.; Ahmad, Zuraini; Chan, Pit Foong (Informatics Publishing Limited and Natural Remedies, 2010)
Ethanolic extract of Annona muricata leaf (AML) was used to investigate its anti-inflammatory and antinociceptive activities by using carrageenan - induced oedema model and acetic acid induced writhing test. AML exhibited significant and dose-dependent anti-inflammatory activity at a dose of 10, 30, 100 and 300 mg/kg when administered orally. It is also demonstrated that the intraperitoneal administration of AML at a dose of 30, 100 and 300 mg/kg produced significant inhibition of abdominal constriction induced with 0.6% (v/v) acetic acid in dose dependent manner. These results indicate that AML exhibits significant anti-inflammatory and antinociceptive effects.